2010
DOI: 10.1017/s1368980010001242
|View full text |Cite
|
Sign up to set email alerts
|

Long-term sustainability of a worksite canteen intervention of serving more fruit and vegetables

Abstract: Objective: To analyse the 5-year sustainability of a worksite canteen intervention of serving more fruit and vegetables (F&V). Design: Average F&V consumption per customer per meal per day was assessed in five worksite canteens by weighing F&V served and subtracting waste. Data were collected by the canteen staff during a 3-week continuous period and compared to data from the same five canteens measured at baseline, at end point and at 1-year follow-up. The intervention used a participatory and empowering appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
57
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(63 citation statements)
references
References 21 publications
6
57
0
Order By: Relevance
“…free available fruit and serving more fruit and vegetables at worksite canteens) (6)(7)(8) . Moreover, these kinds of environmental-level initiatives may not be restricted to a self-selected subset of motivated individuals who choose to participate in worksite health promotion programmes but rather has the potential to impact the entire worksite population (9) .…”
mentioning
confidence: 99%
“…free available fruit and serving more fruit and vegetables at worksite canteens) (6)(7)(8) . Moreover, these kinds of environmental-level initiatives may not be restricted to a self-selected subset of motivated individuals who choose to participate in worksite health promotion programmes but rather has the potential to impact the entire worksite population (9) .…”
mentioning
confidence: 99%
“…The implementation of health-promoting initiatives is an ongoing challenge for public health, and the workplace setting is no exception (Thorsen et al, 2010). This study suggests that fruit boxes may be likely to be implemented in workplaces, provided that three main criteria are met: management support, a receptive culture and sufficient resources.…”
Section: Discussionmentioning
confidence: 91%
“…Studies have shown that by introducing changes in the workplace that promote a healthy diet, there can be beneficial outcomes in terms of dietary behaviours for employees (Mhurchu et al, 2010). One way of improving employees' diets is the provision of fruit in the workplace (Alinia et al, 2009;Hutchinson et al, 2013;Thorsen et al, 2010). Introducing fruit into the workplace is a simple way of providing employees with access to a healthy snack option that does not require preparation or cooking (Alinia et al, 2009(Alinia et al, , 2010.…”
Section: Introductionmentioning
confidence: 99%
“…These include behavioral/nutrition education interventions [22,2439,41,42,59], increasing access to F&V [37,45,47,49,6062], and multilevel interventions that combine environmental strategies with behavioral nutrition programs [30,37,46,5055,60,62]. Systematic reviews of F&V interventions at worksites have concluded that workplace health promotion efforts need to include both educational and environmental changes to have a significant impact on dietary behavior [23,48,56].…”
Section: Introductionmentioning
confidence: 99%
“…Most environmental worksite interventions to increase F&V intake have focused on changing cafeteria or vending offerings and/or making fresh fruit available at no cost to employees [45,4749,60,61]. No studies have evaluated the implementation of regular, mobile, fresh F&V markets at worksites.…”
Section: Introductionmentioning
confidence: 99%